IMPLEMENTASI DAN OPTIMASI JARINGAN FTTB GPON PADA APARTEMEN SUNTER PARK VIEV - Mulia, Adam; Latifah, Fitri (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
As the demand for high-speed internet access increases in vertical residential environments, the implementation of efficient and reliable network infrastructure becomes essential. This study discusses the deployment and optimization of a Fiber To The Building (FTTB) network using Gigabit Passive Optical Network (GPON) technology at Sunter Park View Apartment, North Jakarta. The research aims to replace the existing EPON-based system, which has limitations in bandwidth capacity and service distribution efficiency. The methodology involves field observation, interviews with technical teams, as well as simulation and testing using the OptiSystem software. The GPON network design covers the entire access network, from the central Optical Line Terminal (OLT) to the Optical Distribution Point (ODP), employing a configuration of 1:4 and 1:32 splitters. The simulation and testing results indicate that the power link budget values remain within the tolerance limits set by Biznet Networks, demonstrating that the network is feasible and optimal for operation. This study concludes that GPON technology offers superior efficiency, service capacity, and network stability compared to EPON, and is suitable for implementation in apartment-scale internet distribution systems.